Stochastic finite element analysis of plates with the Certain Generalized Stresses Method. (July 2016) - Mahjudin, Mahyunirsyah; Lardeur, Pascal; Druesne, Frédéric; Katili, Irwan
Highlights: The Certain Generalized Stresses Method for membrane and bending plates is presented. The CGSM is a non-intrusive method that requires only one finite element analysis with several load cases. The first example is a square membrane plate with a circular hole under tension. The second example is a simply supported square bending plate under uniformly distributed load. The CGSM is efficient in terms of quality of results and computational time. Abstract: The Certain Generalized Stresses Method (CGSM) takes into account variability in static finite element analysis. The CGSM is dedicated to thin-walled structures: bars, beams, plates and shells. The objective of this paper is to present and evaluate a methodology based on the CGSM, for the static finite element analysis of plates with variability. The CGSM is a non-intrusive method that requires only one finite element analysis with some load cases to calculate the variability of mechanical quantities of interest. The statistical results: mean value, standard deviation and distribution are obtained by Monte Carlo simulations, using a semi-analytical formula. Two examples are treated: a square plate with a circular hole under tension and a simply supported square bending plate under uniformly distributed load. The method provides results of good quality and is very economical from a computational time point of view.